CARDIOGENESIS CHANGES AFTER THE PLUMBIC ACETATE IMPACT IN RATS UNDER THE CORRECTION CONDITIONS IN THE EXPERIMENT - Shatornaya, V.F.; Nefyodova, O.O.; Nefyodov, O.O.; Kolosova, I.I.; Major, V.V.; Kuznetsova, O.V.; Demidenko, Yu.V.; Yeroshenko, G.A. (World of Medicine and Biology, 2020)
The purpose of the study was to determine the morphogenetic patterns of forming the effects of isolated plumbic acetate impact and the combined action of plumbic acetate with metal citrates on the development of the rat embryo’s heart in the experiment. With isolated plumbic acetate administering to pregnant females in a dose of 0.05 mg/kg, the thickness reduction of the compact myocardium, walls of the right and the left ventricles in the embryo’s heart occurs. The most sensitive to the plumbic acetate impact is the heart right ventricle wall, where not only the compact myocardium thinning, but also the increased number and diameter of the functioning vessels are observed. The combined administration of plumbic acetate with the gold citrate solution (or iron citrate/silver citrate) prevents the negative effect of plumbic acetate on the overall course of cardiogenesis in rat embryos under the experimental conditions and indicates their bioanagonism.
Keywords: embryogenesis; cardiogenesis; plumbic acetate; gold citrate; silver citrate; iron citrate